External regulation, independent director attendance, and governance effects - Leilei Song; Gary Gang Tian; Guanmin Liao (China Journal of Accounting Research, 2021)
In this study we examine how the regulation of director attendance disciplines directors' behavior, and consider the governance effect of such regulations. This examination exploits the differences between the requirements for director attendance at board meetings enacted by the Shanghai Stock Exchange (SHSE) and by the Shenzhen Stock Exchange (SZSE). Using a difference-in-differences model with a sample of A-share listed firms from 2006 to 2017, we document that the rate of meeting attendance by independent directors who serve with firms listed on the SHSE (SHIDs) has increased significantly since the exchange's enforcement of the regulation on attendance. This positive effect has been more pronounced for independent directors with legal backgrounds. Further investigations find that the regulation of attendance plays a corporate governance role through the mechanism of enhanced monitoring. The attendance regulation increases the SHIDs likelihood of casting dissenting votes, and it leads to both better accounting performance and higher firm value. In addition, SHIDs are more likely to depart from firms listed on the SHSE, and to transfer their directorships to firms listed on the SZSE, which has a less constraining attendance requirement. Our findings provide evidence of how external regulation shapes director attendance and voting behavior in emerging markets.
Keywords: 650; Corporate governance effect; External regulation; Independent director board meeting attendance; Independent director dissent